Effects of Halopriming and Hydropriming on Seed Germination and Seedling Emergence of Chilli (Capsicum frutescens) - Poudel, Surakshya; Paudel, Swastika; Rijal, Bipin; Shrestha, Avishek; Kafle, Aarati; Blon, Norgin (Journal of Agriculture and Resource Management, 2024)
Capsicum frutescens plants are exposed to a variety of environmental factors, including salinity, drought, high temperatures, and others, which have a detrimental effect on plant development and productivity. There exist several physiological and non-physiological techniques to enhance the germination process, which can help overcome environmental constraints and improve seed performance. Seed priming is a pre-sowing seed treatment that provides regulated hydration of seeds to absorb water and pass through the initial stage of germination, hence allowing seed to germinate more efficiently. This enhances the pre-germinative metabolic process and hastens germination. To evaluate the effect of hydropriming and halopriming methods on the seed germination and seedling emergence of Capsicum frutescens an experiment was carried out in Controlled Randomized Design (CRD) in the lab of College of Natural Resource Management, Bardibas, Mahottari. Seeds of capsicum was used with 7 treatments consisting of 3 replications in the experiment. Treatments includes T1: Halopriming with 1% KNO3(Potassium Nitrate), T2: Halopriming with 2% KNO3, T3: Halopriming with 3% KNO3, T4: Halopriming with 1% NaCl(Sodium chloride), T5: Halopriming with 2% NaCl, T6: Halopriming with 3% NaCl, T7: Hydropriming with normal water. Seeds were soaked in prepared solution of KNO3 and NaCl at different concentrations for 24 hours at lab temperature. The findings of this experiment suggests that halopriming treatments with KNO3 may improve root and shoot emergence and 50% germination as compared to seed treated with NaCl. As evidenced by the slower growth of radicle and plumule in seed treated with NaCl and hydropriming, it was found that seed primed with 3% KNO3 had these characteristics.